Evaluación de la calidad de ovocitos bovinos con la técnica de la vitrificación en el laboratorio de biotecnología de la reproducción de la Universidad Técnica de Cotopaxi - Víctor Miguel, Lliguisupa Landin (2015)
This research was conducted in the laboratory of Reproductive Biotechnology Center of Experimentation and Production Salache "CEYPSA" Technical University of Cotopaxi. The main objective of this study was to evaluate the effect of vitrification in so far as of the quality and maturity of bovine oocytes. Collect it 10 ovaries of cows slaughtered in the slaughterhouse Saquisili, of which a total of 114 oocytes was obtained was collected, obtaining 50 of category 1, 37 category II, 27 category III. To conduct the research took only oocytes category I. washing the 50 Category I oocytes was performed with holding and proceeded to vitrification in straws was stored previously stretched in thermal plate and placed in a nitrogen tank, then proceeded to the desvitrification of all oocytes and was re-evaluated in the stereoscope and the result was that 50 category I oocytes showed no improvement in their quality and maturity after vitrification….